The structural characteristics of dietary fibers from Tremella fuciformis and their hypolipidemic effects in mice - Shanshan Zhang; Xinle Xu; Xu Cao; Tingting Liu (Food Science and Human Wellness)
In this study, Tremella fuciformis residues as raw material, dietary fibers from tremella were prepared by multiple enzymes. The structure of dietary fibers from tremella was studied by Fourier transform infrared (FTIR), X-ray diffraction analysis (XRD) and scanning electron microscopy (SEM). We analyzed their lipid-lowering properties in vitro (water holding, oil holding swelling cholesterol and sodium cholate binding capacitises) and the hypolipidemic effects in mice. The results showed that tremella dietary fibers presented the infrared absorption spectrum characteristics of polysaccharides and the characteristic diffraction peaks of cellulose type I. SEM results indicated that the surface of insoluble dietary fiber (IDF) was porous, while the soluble dietary fiber (SDF) was relatively compact and spongy. IDF exhibited significantly higher water holding, oil holding, and swelling binding capacities than the corresponding SDF. However, SDF exhibited significantly higher viscosity than IDF. The results showed tremella dietary fibers were significant in swelling, water holding and oil holding, cholesterol and bile acids. In vivo experiment results in mice indicated that SDF has the best effect on hyperlipidemia mice than IDF and total dietary fiber (TDF). SDF showed that the total cholesterol (TC), triglyceride (TG) and low density lipoprotein cholesterol (LDL-C) contents dropped by 28.33 %, 18.65 %, and 48.97 %, respectively, while high density lipoprotein cholesterol (HDL-C) content increased by 43.80 %. Compared with the high-fat control (HCM) group, the arteriosclerosis index (AI) and liver index (LI) of the SDF group mice showed significant differences, indicating that SDF has a good auxiliary effect of lowering blood lipids. The administration of tremella fibers improved the lipid metabolism disorderly situation of hyperlipidemia mice. These results provide a reference for further research and rational development of T. fuciformis.